Pembunuhan Dalam Perspektif Pasal 338 KUHP Dan Hadits Samurah - mayang, Dewi; Arifin, Tajul (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
This research will discuss the legal analysis of article 338 of the Criminal Code relating to murder, as well as the legal perspective provided by the hadith from Samurah Radhiyallahu'anhu. Article 338 of the Criminal Code is a criminal law provision in Indonesia which regulates murder. In this context, an analysis will be carried out on the legal implications of the article, both in its application and interpretation. Apart from that, this abstract will also discuss the perspective of Islamic law regarding murder based on hadith from Samurah Radhiyallahu'anhu. Hadith is the second source of law in Islam after the Koran and is often a guide in interpreting various legal issues. By analyzing this hadith, we will consider how Islamic law views the act of murder and the factors that influence it. Through this approach, this abstract will present a comprehensive understanding of murder in the context of Indonesian positive law and Islamic law. By considering legal perspectives from these two different sources, it is hoped that we can provide a broader and deeper view of the issue of murder in the legal realm..